Current Update in Asian Rhinoplasty - Ishii, Clyde H. (Wolters Kluwer Health, 2014)
SUMMARY: There has been a tremendous growth of cosmetic surgery among Asians worldwide. Rhinoplasty is second only to blepharoplasty in terms of popularity among Asians regarding cosmetic surgical procedures. Most Asians seek to improve their appearance while maintaining the essential features of their ethnicity. There are considerable ethnic nasal and facial variations in this population alone. Successful rhinoplasty in Asians must take into account underlying anatomic differences between Asians and whites. Due to ethnic variations, cultural differences, and occasional language barriers, careful preoperative counseling is necessary to align the patient’s expectations with the limitations of the procedure. This article will review the many facets of Asian rhinoplasty as it is practiced today.